AIDS AND HIV DISEASE ITS EFFECTS ON THE HUMAN ORGANISM, TRANSMISSION WAYS AND PREVENTION - Kilichev Jasurbek Fayzullayevich; Kabulov Boburbek Dilshodbekovich; Rustamov Ravshan Umidovich (Galaxy International Interdisciplinary Research Journal, 2022)
Today, the disease "Acquired Immune Deficiency Syndrome" and "Acquired Immune Deficiency" is growing rapidly throughout the world region. It is very necessary that we get such diseases. What is AIDS and HIV disease? How does it affect patients? Will people who are infected with this disease recover? How can we prevent such a disease?